An economic evaluation of an early palliative care intervention among patients with advanced cancer - Maessen, Maud; Fliedner, Monica C.; Gahl, Brigitta; Maier, Marina; Aebersold, Daniel M.; Zwahlen, Susanne; Eychmüller, Steffen (Swiss medical weekly, 2024)
BACKGROUND: Early integration of palliative care into oncology care has shown positive effects on patient symptoms and quality of life. It may also reduce health care costs. However given the heterogeneity of settings and interventions and the lack of information on the minimally effective dose for influencing care utilisation and costs, it remains uncertain whether early palliative care reduces costs. OBJECTIVES: We sought to determine whether an early palliative care intervention integrated in usual oncology care in a Swiss hospital setting reduced utilisation and costs of health care in the last month of life when compared with usual oncology care alone. METHODS: We performed a cost-consequences analysis alongside a multicentre trial. We extracted costs from administrative health insurance data and health care utilisation from family caregiver surveys to compare two study arms: usual oncology care and usual oncology care plus the palliative care intervention. The intervention consisted of a single-structured, multiprofessional conversation with the patient about symptoms, end-of-life decisions, network building and support for carers (SENS). The early palliative care intervention was performed within 16 weeks of the diagnosis of a tumour stage not amenable or responsive to curative treatment. RESULTS: We included 58 participants with advanced cancer in our economic evaluation study. Median overall health care costs in the last month of life were 7892 Swiss Francs (CHF) (interquartile range: CHF 5637–13,489) in the intervention arm and CHF 8492 [CHF 5411–12,012] in the control arm. The average total intervention treatment cost CHF 380 per patient. Integrating an early palliative care intervention into usual oncology care showed no significant difference in health care utilisation or overall health care costs between intervention and control arms (p = 0.98). CONCLUSION: Although early palliative care is often presented as a cost-reducing care service, we could not show a significant effect of the SENS intervention on health care utilisation and costs in the last month of life. However, it may be that the intervention was not intensive enough, the timeframe too short or the study population too small for measurable effects. Patients appreciated the intervention. Single-structured early palliative care interventions are easy to implement in clinical practice and present low treatment costs. Further research about the economic impact of early palliative care should focus on extracting large, detailed cost databases showing potential shifts in cost and cost-effectiveness. Clinical Trials. gov Identifier: NCT01983956